2015
DOI: 10.13075/ijomeh.1896.00512
|View full text |Cite
|
Sign up to set email alerts
|

Byssinosis and COPD rates among factory workers manufacturing hemp and jute

Abstract: Because of high exposures to jute and hemp dusts that are associated with high byssinosis rates, personal protection and environmental hygiene is crucial to prevention of byssinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…(3, 9) Hemp workers with exposure to organic aerosols have higher IgE titers and chronic respiratory symptoms compared to non-exposed hemp workers (10) and a high prevalence of work-related respiratory conditions, such as byssinosis. (3, 1114) Like hemp workers, cannabis industry workers are expected to be exposed to products, such as leaves, buds, sap/exudate, flowers, and pollen and their associated plant pathogens, including bacteria and fungi, when handling the plant during cultivation and processing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…(3, 9) Hemp workers with exposure to organic aerosols have higher IgE titers and chronic respiratory symptoms compared to non-exposed hemp workers (10) and a high prevalence of work-related respiratory conditions, such as byssinosis. (3, 1114) Like hemp workers, cannabis industry workers are expected to be exposed to products, such as leaves, buds, sap/exudate, flowers, and pollen and their associated plant pathogens, including bacteria and fungi, when handling the plant during cultivation and processing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are almost similar to our observations. The prevalence of obstructive lung disease was much less (0.8%) than that of other studies (17% -28%) [12]. It may happen that the workers suffering from chronic obstructive pulmonary disease (COPD) are considered disable and removed from job.…”
Section: Discussionmentioning
confidence: 84%
“…16 Other studies have shown that flu-like symptoms are common among cotton workers and farmers and workers in food processing industries, who are exposed to other biological active agents in bioaerosols. [17][18][19][20][21] Melbostad and Eduard 9 showed that farmers who were exposed to fungal spores in their work environment had more eye symptoms and cough compared to controls. Work-related cough with phlegm and runny nose were shown to be more common among Russian trawler fishermen who work with fish filleting on board compared to controls.…”
Section: Control Cases Nmentioning
confidence: 99%